Intention-based fairness preferences in two-player contests - Magnus Hoffmann; Martin Kolmar (Center for Economic Studies and ifo Institute (CESifo), 2013)
We analyze equilibria of two-player contests where players have intention-based preferences. We find that players invest more effort compared to the case with selfish preferences and are even willing to exert effort when the monetary value of the prize converges to zero. As a consequence, overdissipation occurs if the value of the prize is sufficiently small.
Keywords: D03; D72; D74; 330; contests; intention-based fairness preferences; Wettbewerb; Spieltheorie; Gerechtigkeit; Präferenztheorie; Theorie